Immunohistochemical Study Using Monoclonal VE1 Antibody Can Substitute the Molecular Tests for Apprehension of BRAF V600E Mutation in Patients with Non-small-Cell Lung Carcinoma - Hadeel Abdul Elah Karbel; Sura Salman Ejam; Ali Zaki Naji (Analytical Cellular Pathology)
In patients with non-small-cell lung carcinoma (NSCLC), the analysis of BRAF V600E mutation has become more and more applied since the introduction of many mutation-targeted medications. In this regard, the advantage of immunohistochemistry (IHC) as a reliable diagnostic test substitute to other molecular studies has not been approved yet. Objective. To examine the dependability of using immunohistochemical method utilizing monoclonal VE1 antibody in the detection of BRAF V600 E mutation in patients with non-small-cell lung carcinoma and compare the results there with that of polymerase chain reaction (SSCP-PCR). Materials and Methods. We retrospectively identified 53 patients of whom their histopathological diagnosis was non-small-cell carcinoma of different types. Evaluation of BRAF V600E mutation was assessed using polymerase chain reaction (SSCP-PCR) and IHC using VE1 antibody. This approach was applied to all cases under the study. Results. Among the 53 NSCLC samples, only 5 (9.3%) cases harbored BRAF V600E mutation, 80% were of adenocarcinoma type, and the rest (20%) was of squamous cell carcinoma. IHC analysis for VE1 was positive in 4 out of 5 (80%) BRAF-mutated tumors and negative in all nonmutated BRAF V600 E NSCLC. Conclusion. Our results revealed that VE1 antibody IHC analysis is a promising technique that can be used to detect BRAF V600-mutated NSCLC with relatively high specificity and sensitivity and might become a potential alternative to the current molecular biological methods that are in use for this purpose.